Impacts of historic anthropogenic aerosol forcing on large climate ensembles through the lens of poleward energy transport - Needham, Michael Robert, author; Randall, David A., advisor; Rugenstein, Maria, committee member; van Leeuwen, Peter Jan, committee member; Rugenstein, Jeremy, committee member (Colorado State University. Libraries, 2024)
In discussions of the human impact on Earth's climate, aerosols receive much less attention than greenhouse gases. And yet, the change in the global mean effective radiative forcing from anthropogenic aerosols was roughly of the same magnitude (but of opposite sign) as the change in greenhouse gases throughout much of the twentieth century. Aerosols also represent the largest uncertainty in the effective radiative forcing, due to their complex interactions with clouds and solar radiation. Complicating this even further, aerosols are relatively short-lived within the atmosphere, and thus exhibit a large degree of variability in space and time. This dissertation presents a set of studies which investigate the ways in which historic anthropogenic aerosols may have impacted the Earth's weather and climate, through the analysis of a large number historic climate model simulations which comprise so-called large ensembles. Analysis of these ensembles allows for the isolation of some forced signal (e.g., the influence of aerosols) from the noise (i.e., the background variability of the model). This leads to conclusions through the analysis of summary statistics across members of the ensemble population which would be impossible to make based on only one or a few simulations. In particular, these studies show that the emission of aerosol precursors from Europe and North America increased the northward transport of heat from the southern into the northern hemisphere in an ensemble of simulations performed with version 2 of the Community Earth System Model (CESM2). The additional heat transport was in excess of 0.25 PW. This is an increase of at least 4-5% compared to the baseline maximum transport of between 5-6 PW which occurs in the mid-latitudes. At latitudes away from these maxima, the increase was a much larger percentage of the total. This anomalous northward energy transport was accomplished by changes in both atmospheric and oceanic processes. These include a southward shift of the Intertropical Convergence Zone (ITCZ) associated with changes in the Hadley cells; an increase in the frequency of extratropical cyclones in the north Atlantic; a strengthening of the Atlantic Meridional Overturning Circulation (AMOC); as well as changes to multiple ocean processes across the Indo-Pacific. Comparison of these results to the literature indicates that this modeled response to aerosols in CESM2 is likely too large. Furthermore, analysis of two additional large ensembles reveals that this over-sensitivity of CESM2 cannot be due to some deficiency in the model. Instead, it is demonstrated that the difference is the result of changes to the historical emission estimates between phase 5 and phase 6 of the Coupled Model Intercomparison Project (i.e., CMIP5 and CMIP6). This finding leads to the hypothesis that the higher interannual variability associated with a change from decadal-scale CMIP5 emissions to annual-scale CMIP6 emissions is the ultimate cause of the overzealous response of the model. Testing this hypothesis likely will provide the most fertile ground for future work.
Keywords: AMOC; aerosol; climate